Does contracting matter? The determinants of contracting and contracting's effects on cost efficiency in United States fixed-route bus transit service - Iseki, Hiroyuki (ProQuest Dissertations & Theses, 2004)
This dissertation is an empirical study of the factors that compel transit agencies to contract out fixed-route bus transit service, and whether and how contracting improves cost efficiency. I use an instrumental variable technique in a two-stage multiple regression analysis to address the endogeneity problem between cost efficiency and agencies' decisions to contract. Most previous research has focused mainly on measuring cost savings of contracted service, and treated contracting as a simple make-or-buy decision. However, my first-stage agency decision making model shows that it is important to distinguish agencies that contract out only a small portion of their service from those that contract out all service since different sets of factors determine the level of contracting an agency chooses. The second-stage cost efficiency model shows modest cost efficiency improvement in the order of 7.8 percent and 5.5 percent for an average agency through partial- and full-contracting respectively. However, this improvement is not universal, because the effects of contracting on cost efficiency vary by factors such as peak-to-base ratio, agency size, the wage gap between bus operators in the public and private sectors, and agency type. Large agencies, whose contracting decisions are more managerial and less subject to political and institutional factors, tend to contract out only part of the service, thereby adjusting their overall size to offset diseconomies of scale and to increase the operating efficiency of in-house service; they do not necessarily gain direct cost savings through contracted service. In contrast, small agencies, whose decisions are also influenced by institutional factors (agency type, structure of board of directors, and state laws governing local governments), tend to contract out all service to increase cost efficiency primarily by saving on labor costs. In contrast to the past studies on the topic, some of which are ideologically driven, I find that a contracting strategy can be a viable option to improve cost efficiency in transit service, but only when a transit agency carefully chooses the service level to contract based on an adequate assessment of its conditions.